Perubahan Fungsi Tari Ngadu Tanduk Sebagai Tari Tradisional Masyarakat Desa Siulak Panjang Kabupaten Kerinci - Sevi Sovia; Indrayuda Indrayuda (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study aims to describe and analyze the Changes in the Function of Ngadu Tanduk Dance as a Traditional Dance of the Siulak Panjang Village Community. The type of research used is qualitative with a descriptive method. The instrument of this study is the researcher himself, with supporting instruments such as stationery and mobile phones. The data collection techniques used are literature studies, observations, interviews, and documentation. The data analysis techniques used include data collection, data reduction, data presentation, and data verification/conclusion drawn. The results of the study show that the Ngadu Tanduk Dance is a dance that originated from Siulak Panjang Village, Siulak District, Kerinci Jambi Regency. The change in the function of the Ngadu Tanduk Dance reflects the social and cultural dynamics of the local community that continues to develop. This dance initially only had a traditional function but now it also has an entertainment and performance function. Changes in function in the Ngadu Tanduk Dance are influenced by internal and external factors that interact in the context of the community. The internal factors that affect are changes in people's mindsets and the need for entertainment and cultural identity. While external factors are changes in the agricultural cycle and the influence of globalization and modernization.